PENGARUH FASILITAS BELAJAR DAN PERAN GURU TERHADAP HASIL BELAJAR ONLINE SISWA - Ani Setiani; Yudho Ramafrizal S; Leni Maryani; Veri Aryanto Sopiansah; Deden Regito (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
This study aims to determine the effect of learning facilities and the role of teachers on online learning outcomes in odd semester economic subjects in class X BDP SMK Pasundan 4 Bandung. The method used in this research is a survey. The subjects in this study used a sample of 56 students. Analysis of the data used is descriptive analysis, classical assumption test and hypothesis testing through multiple linear regression calculation and coefficient of determination with the help of SPSS 25.0 for Windows. From the results of research using descriptive analysis, it is obtained that the average score recapitulation of respondents regarding learning facilities is in the